Modeling the life cycle of the human brain - Budday, Silvia; Kuhl, Ellen (Current Opinion in Biomedical Engineering, 2020)
In recent years, computational mechanics have become a powerful tool to study and predict the behavior of the human brain. Yet, an important challenge that remains unaddressed is that brain tissue is not a constant uniform material. Throughout its life time, our brain’s microstructure, mechanical properties, and macroscopic shape keep changing in close relation to brain function. In this review, we summarize the evolution of various microscopic and macroscopic features during brain development and aging. We discuss how to use mechanical models to translate processes on the microscopic scale into the evolution of mechanical properties and brain shape on the macroscopic scale. In addition, we propose how to incorporate additional coupling effects that arise from the ‘mechanosensitivity’ of brain cells. Considering the entire life cycle of the human brain will be critical to refine existing brain models towards personalized simulations of brain injury, brain damage, and brain protectio
Keywords: brain development; brain aging; nonlinear continuum mechanics; mechanosensing; growth; coupled problems